Perbaikan Proses Bisnis Pembuatan Laporan Produksi Harian untuk Memperpendek Lead Time pada Perusahaan Manufaktur Mobil - Anastasia Lidya Maukar (JIE Scientific Journal on Research and Application of Industrial System, 2021)
This research was conducted at a four-wheeled vehicle manufacturing company located in Jakarta. The average lead time for making the Plant 2 Daily Production Report is currently around 12 minutes. With the long reporting time, this process is considered less efficient. In this research, business process improvement will be carried out by identifying non value-added activities and using business process improvement methodology. In improving the reporting process, Excel Macros will be used. After the implementation of business process improvements, the average time for making Daily Production Reports is reduced to 4 minutes or there is a time saving of 67%.